Lexical and grammatical development in trilingual speakers of isiXhosa, English and Afrikaans - Potgieter, Anneke P. (South African journal of communication disorders, 2016)
Background: There is a dearth of normative data on linguistic development among child speakers of Southern African languages, especially in the case of the multilingual children who constitute the largest part of this population. This inevitably impacts on the accuracy of developmental assessments of such speakers. Already negative lay opinion on the effect of early multilingualism on language development rates could be exacerbated by the lack of developmental data, ultimately affecting choices regarding home and school language policies.Objectives: To establish whether trilinguals necessarily exhibit developmental delay when compared to monolinguals and, if so, whether this delay (1) occurs in terms of both lexical and grammatical development; and (2) in all three the trilinguals’ languages, regardless of input quantity.Method: Focusing on isiXhosa, South African English and Afrikaans, the study involved a comparison of 11 four-year-old developing trilinguals’ acquisition of vocabulary and passive constructions with that of 10 age-matched monolingual speakers of each language.Results: The trilinguals proved to be monolingual-like in their lexical development in the language to which, on average, they had been exposed most over time, that is, isiXhosa. No developmental delay was found in the trilinguals’ acquisition of passive constructions, regardless of the language of testing.Conclusion: As previously found for bilingual development, necessarily reduced quantity of exposure does not hinder lexical development in the trilinguals’ input dominant language. The overall lack of delay in their acquisition of the passive is interpreted as possible evidence of cross-linguistic bootstrapping and support for early multilingual exposure.